The ultra vires doctrine does - it exist in Malaysia? / Margare Rossy Tonek - Tonek, Margare Rossy (Faculty of Law, 1985)
A company which owes its incorporation to statutory authority Cannot effectively do anything beyond the powers expressly or impliedly conferred upon it by its statute or memorandum of association. Any act beyond that would be ineffective even if it were to be agreed upon by all members. A company, therefore, unlike a natural person has limited capacity. Any purported acts beyond the stipulated clause would be considered ultra-vires and be absolutely void. 1 The purpose of this restriction is two-fold : First, to protect investors in the company so that they may know the objects in which their money is employed; and secondly, to protect the credit on by ensuring that the company's funds, to which they look for payment, are not utilised for unauthorised activities. 2 The term ultra vires is also used to describe the situation when the directors have exceeded the authority delegated to them. Compare this with the position when a company does an act outside its memorandum or article. The effects of these acts by the company are' as follows respectively When a company exceeds its powers, it is not bound by its contracts because it lacks legal capacity to incur responsibility for it. Similarly, when the directors go beyond their powers, the company is not bound because their agents have exceeded their authority. However, unless the company's own powers are exceeded, no question of capacity arises and the company may ratify what the directors have done, and may be unable to set up the director's lack of actual authority when they have acted within their usual or ostensible authority.3